2021
DOI: 10.1002/uog.22026
|View full text |Cite
|
Sign up to set email alerts
|

Universal chromosomal microarray analysis reveals high proportion of copy‐number variants in low‐risk pregnancies

Abstract: What are the novel findings of this work?We calculated the rate of clinically significant chromosomal microarray analysis (CMA) findings in low-risk pregnancies, i.e. pregnancies with normal ultrasound (US) at the time of genetic testing, and found that the rate was relatively high. In addition, we documented later-appearing abnormal US findings and pregnancy outcome in these cases. What are the clinical implications of this work?The findings of this study allow an in-depth understanding of the yield of CMA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 50 publications
(80 reference statements)
6
19
0
Order By: Relevance
“…The chances of identifying variants with uncertain clinical significance and/or lowpenetrant susceptibility loci in these uneventful pregnancies will often be higher than Defining results from genome testing in pregnancy 10 the chance of identifying variants that would clearly have a severe impact on health in childhood (2).…”
Section: Susceptibility Locimentioning
confidence: 99%
“…The chances of identifying variants with uncertain clinical significance and/or lowpenetrant susceptibility loci in these uneventful pregnancies will often be higher than Defining results from genome testing in pregnancy 10 the chance of identifying variants that would clearly have a severe impact on health in childhood (2).…”
Section: Susceptibility Locimentioning
confidence: 99%
“…In particular, low‐level mosaicism (<15%‐20%), foetal‐placental discrepancies and the UPD generated by embryo rescue have been reported to be responsible for the increased risk of erroneous diagnoses 4,5 . Recently, improvements have been made in the field of molecular genetics technologies such as quantitative fluorescent polymerase chain reaction (QF‐PCR), fluorescence in situ hybridization analysis (FISH), CMA and next‐generation sequencing so that supplementary analyses on amniotic fluid or cord blood are often performed to confirm the true foetal involvement and its clinical significance 6‐10 . Nevertheless, even CM thought to be confined to the placenta may reflect a cryptic foetal mosaicism that may or may not give rise to phenotypic consequences, or lead to placental dysfunction related to foetal growth restriction 11,12 …”
Section: Introductionmentioning
confidence: 99%
“…4,5 Recently, improvements have been made in the field of molecular genetics technologies such as quantitative fluorescent polymerase chain reaction (QF-PCR), fluorescence in situ hybridization analysis (FISH), CMA and next-generation sequencing so that supplementary analyses on amniotic fluid or cord blood are often performed to confirm the true foetal involvement and its clinical significance. [6][7][8][9][10] Nevertheless, even CM thought to be confined to the placenta may reflect a cryptic foetal mosaicism that may or may not give rise to phenotypic consequences, or lead to placental dysfunction related to foetal growth restriction. 11,12 Thus, based on the unclear clinical significance of CM and limited data about CM in prenatal diagnosis, it is necessary to understand more comprehensively the potential correlation between CM and its phenotypic effects.…”
mentioning
confidence: 99%
“…A recent study by Stern and colleagues found that 1% of a-priori low-risk pregnancies could have an abnormal chromosomal microarray analysis (CMA) result 1 . These findings are congruent with those of previous studies 2 and raise the question of the optimal genetic approach for low-risk pregnancies.…”
Section: Do We Need To Rethink Our Standard Genetic Approach For Low-risk Pregnancies?mentioning
confidence: 99%